Enhanced Neurite Outgrowth on a Multiblock Conductive Nerve Scaffold with Self‐Powered Electrical Stimulation. Issue 10 (3rd April 2019) - Sun, Yi; Quan, Qi; Meng, Haoye; Zheng, Yudong; Peng, Jiang; Hu, Yaxin; Feng, Zhaoxuan; Sang, Xiao; Qiao, Kun; He, Wei; Chi, Xiaoqi; Zhao, Liang
Abstract: Electrical stimulation (ES) is widely applied to promote nerve regeneration. Currently, metal needles are used to exert external ES, which may cause pain and risk of infection. In this work, a multiblock conductive nerve scaffold with self‐powered ES by the consumption of glucose and oxygen is prepared. The conductive substrate is prepared by in situ polymerization of polypyrrole (PPy) on the nanofibers of bacterial cellulose (BC). Platinum nanoparticles are electrodeposited on the anode side for glucose oxidation, while nitrogen‐doped carbon nanotubes (N‐CNTs) are loaded on the cathode side for oxygen reduction. The scaffold shows good mechanical property, flexibility and conductivity. The scaffold can form a potential difference of above 300 mV between the anode and the cathode in PBS with 5 × 10 −3 m glucose. Dorsal root ganglions cultured on the Pt‐BC/PPy‐N‐CNTs scaffold are 55% longer in mean neurite length than those cultured on BC/PPy. In addition, in vivo study indicates that the Pt‐BC/PPy‐N‐CNTs scaffold promotes nerve regeneration compared with the BC/PPy group. This paper presents a novel design of a nerve scaffold with self‐powered ES. In the future, it can be combined with other features to promote nerve regeneration. Abstract : A multiblock conductive nerve scaffold with self‐powered electrical stimulation by the consumption of glucose and oxygen for nerve regeneration is designed. Glucose is oxidized on the anode part by Pt nanoparticles and oxygen is reduced on the cathode part by nitrogen‐doped carbon nanotubes. The scaffold effectively promotes the outgrowth of neurites.